2016
DOI: 10.21037/jss.2016.09.04
|View full text |Cite
|
Sign up to set email alerts
|

Extraforaminal needle tip position reduces risk of intravascular injection in CT-fluoroscopic lumbar transforaminal epidural steroid injections

Abstract: Background: Lumbar transforaminal epidural steroid injection is a common and effective tool for managing lumbar radicular pain, although accidental intravascular injection can rarely result in paralysis.The purpose of this study is to determine the safest needle tip position for computed tomography (CT)-guided lumbar transforaminal epidural steroid injections as determined by incidence of intravascular injection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…Intravascular distribution of the medication applied is evident in 8-9 % of cases. The risk of this intravascular misinjection was shown in this study to be significantly lower if the needle position was slightly extraforaminally positioned [24]. This shows that a safe and yet effective needle position for the patient should be sought, especially since an absolute needle position is not correlated with success.…”
Section: Discussionmentioning
confidence: 60%
“…Intravascular distribution of the medication applied is evident in 8-9 % of cases. The risk of this intravascular misinjection was shown in this study to be significantly lower if the needle position was slightly extraforaminally positioned [24]. This shows that a safe and yet effective needle position for the patient should be sought, especially since an absolute needle position is not correlated with success.…”
Section: Discussionmentioning
confidence: 60%
“…There is controversy in the literature regarding the ideal needle-tip position. As shown by Yu et al (15), intravascular injection occurred more often when the needle tip was positioned foraminally. Regarding treatment effectiveness, a study by Desai et al (30) demonstrated a significantly better pain reduction with the extension of drugs in the ventral epidural space, achieved more frequently by positioning the needle tip in the superior-anterior rather than the superiorposterior aspect of the neural foramen.…”
Section: Discussionmentioning
confidence: 86%
“…According to a scheme used in previous studies, the needle-tip position was categorized as extraforaminal, junctional, or foraminal ( Fig. 4) in relation to the targeted neural foramen (15). Distances between the needle tip and the nerve root were measured (Fig.…”
Section: Imaging Analysismentioning
confidence: 99%
“…Notably, these epidural injection techniques are not entirely analogous to TFLPs. Percutaneous foraminal epidural injections through Kambin's triangle use a paraspinal posterolateral oblique needle trajectory through the IVF toward the intervertebral disc (Yu et al, ), whereas a TFLP needle should have a course perpendicular (or slightly less) to an IVF seen en face (Nascene et al, ). Despite these different needle trajectories toward the IVF, we propose that as the needle tip reaches the IVF, the middle segment of the posterior IVF crescent should be considered as the safe zone (since it is most devoid of neurovascular structures) and precisely targeted during either type of procedure.…”
Section: Discussionmentioning
confidence: 99%
“…For standardization purposes, we defined this as the parasagittal slice showing the smallest IVF cross-sectional area (Figure 1), as the IVF transitioned over a very short distance from within the central spinal canal to the junctional/extraforaminal space beyond the foramen. This is equivalent to a shallow "foraminal" zone (rather than the "junctional" or "extraforaminal" zones) between the facet and the intervertebral disc or vertebral body, previously demonstrated and defined on axial images by Yu et al, (2016).…”
Section: Methodsmentioning
confidence: 97%